ACCIDENTAL POISONING IN CHILDREN AND ADOLESCENTS ADMITTED TO A REFERRAL TOXICOLOGY DEPARTMENT OF A BRAZILIAN EMERGENCY HOSPITAL - Luciana Vilaça; Fernando Madalena Volpe; Roberto Marini Ladeira (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To describe the profile of children and adolescents admitted for exogenous unintentional poisoning in the emergency room and analyze factors associated with subsequent in-hospital admissions. Methods: This is a cross-sectional study based on hospital records of all subjects up to 19 years-old admitted in 2013 at a specialized toxicology service on a major public emergency hospital due to unintentional intoxication (as reported). Accidents with poisonous animals and insects were excluded. Percentages and frequencies were calculated for the qualitative variables, and measures of central tendency and dispersion for the continuous quantitative variables. Multivariate analysis was performed using binary logistic regression to identify variables associated with subsequent in-hospital admissions. Results: In 2013, 353 cases were reported. Poisonings were more frequent in children 0-4 years-old (72.5%) and in boys (55%). The vast majority was of dwellers of the Metropolitan Region of Belo Horizonte (83%), and 90% of the accidental poisonings occurred at home. 82.7% of the poisonings occurred by oral ingestion, especially of medicinal (36.5%) and cleaning products (29.4% of all poisonings). Only 12.2% of the cases resulted in hospitalization, and only one resulted in death. Residing outside Belo Horizonte (OR=5.20 [95%CI 2.37-11.44]) and poisoning by two or more products (OR=4.29 [95%CI 1.33-13.82]) were considered risk factors for hospitalization. Conclusions: Accidental poisonings occurred most frequently by ingestion of household medications and cleaning products, especially among children under 4 years-old. Preventive strategies should be primarily directed for this prevalent profile.